Tourists' Attitudes Towards Halal Tourism: The Roles of Place Attachment and Religiosity - Maesaroh, Imas; Dewi, Ike Janita; Ginting, Ginta (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2024)
This research aims to analyze tourists' attitudes towards the attributes of halal tourism (HT) destinations, moderated by place attachment and religiosity. This study contributes to the body of research on HT development because the conceptual model includes specific HT destination attributes and integrates place attachment theory and tourist psychographic characteristics (religiosity). This research is quantitative research with 355 respondents. The data were analyzed using Smart PLS. This research resulted in the conclusion that attitude towards HT destination development is influenced by three things, namely 1) attitude towards HT attributes, 2) religiosity of tourists, and 3) place attachment of tourists with the destination. The role of religiosity in forming attitudes towards HT destination development occurs directly and also as a moderator between attitudes towards HT attributes and attitudes towards HT destination development. Meanwhile, the role of place attachment in forming attitudes towards HT destination is a direct influence. In terms of public policymaking, this research provides important insight. The development and determination of HT destinations can receive approval and rejection in different destinations. Tourists can give different responses to the development of HT destinations for different destinations. In making these policies, tourists' opinions are very important to be taken into consideration in developing a tourist destination.